Siddheshwar Mahadev Temple - Ghosh, Ayan (2023)
Siddheshwar Mahadev temple forms part of what was once known as Jairamgir Bawa’s Math, where samadhis of ascetics of the orthodox Giri Smarta sect were erected. The samadhis of the founder (Jairamgir Bawa) and two other ascetics were also built here. The temple overlooks the Banganga Tank and is noted for its arched gateway, grayish-blue basalt walls, pyramidical shikhara, and compact sabha mandap.